Changes in mineral reactivity driven by pore fluid mobility in partially wetted porous media - Harrison, A.; Dipple, G.; Song, W.; Power, I.; Mayer, K.; Beinlich, Andreas; Sinton, D. (Elsevier Science BV, 2017)
Microfluidics experiments were used to examine mineral dissolution-precipitation reactions under evaporative conditions and identify pore-scale processes that control reaction rate. The entrainment of reacting mineral particles by a mobile water-gas interface driven by evaporation dramatically altered the relative abundance of reactive mineral surface area to fluid reservoir volume. This ratio, which directly influences reaction rate and reaction progress, was observed to vary by nearly two orders of magnitude as evaporation progressed in the experiments. Its dynamic evolution may have a correspondingly large impact on mineral-fluid reaction in Earth's shallow subsurface. We predict that the spatial and temporal variability of pore-scale reaction rates will be significant during evaporation, imbibition, or drainage in the vadose zone, with implications for chemical weathering, soil quality, and carbon cycling. Variable reaction rates during particle mobility are likely to be of increased significance as global rainfall patterns and soil moisture contents evolve in response to climate change.